Development of Monopoly Media Based on Culturally Responsive Teaching on an Ecosystem Theme for Elementary School Students - Fitri Anjaswuri; Indri Yani; Nurlinda Safitri; Ilmi Zajuli Ichsan (Jurnal Penelitian Pendidikan IPA, 2023)
Development of monopoly media based on culturally responsive teaching on ecosystem themes for fifth-grade elementary school students using the Research and Development method with the ADDIE model. Analysis of needs and conditions is focused on real conditions apart from innovative learning strategies, but the use of innovative and interesting learning media or learning resources makes learning more meaningful. The development of innovative learning media is an alternative to solving problems that occur in the learning process, especially for students. Culturally responsive teaching is an effective learning approach that is in line with curriculum demands. Monopoly media based on culturally responsive teaching on ecosystem material produces valid and responsive categories that are effective for users. The final results of the validation by material experts and media experts obtained quite high results in the valid category so that the product could be tested. The teacher's response resulted in a percentage of 100% and students were also positive towards this media with a percentage of 82.17%. Teachers and students agree that monopoly media based on culturally responsive teaching on ecosystem material is valid and suitable for use.